OPEN EDUCATIONAL ENVIRONMENT AS AN INTEGRAL PART OF INNOVATIVE EDUCATION - Perminova, Vladyslava; Sikaliuk, Anzhela; Lytvyn, Svitlana (Науковий вісник Полісся, 2017)
Urgency of research. The current stage of development of Ukrainian educational system is characterized by its integration into the world educational environment. This is followed by creation of a new paradigm of education aimed at developing an educated, creative person who has clear national convictions. Target setting. The urgent task is to transform the educational environment of higher educational establishment in highly organized community of progressive-minded national value systems, productive activity, able to ensure the conditions of personality who solves professional problems competently, has active citizenship behavior and positive national identity. Actual scientific researches and issues analysis. Environment, including an educational one, as a part of the environmental and objective environment is studied by foreign scholars (J. Gibson, W. Mace, T. Meng, M. Tourves, V. Yasvin) and domestic researchers (G. Ball, J. Bekh, E. Bondarevskaya, S. Maximov, E. Piekhota, V. Rybalko, V. Semychenko, V. Serikov, S. Sysoiev). Uninvestigated parts of general matters defining. Modern innovative educational environment of professional institutions appears as a dialectical combination of unity and diversity. It is extremely urgent to optimize the innovative educational environment of modern professional educational establishment institutions through the organizing of a system of interacting open spaces. The research objective. The main objective of our research is to implement the search for unity between the social educational needs at various levels and the need for the staff of educational establishments in the development of the most valuable in a context and methodological aspects of innovative activity - in the effective use of the open space system in the education of students. The statement of basic materials. The contradictions of the traditional education system are the most important objective factor, which embarrasses the conductive creation of a system of the open educational environment. Conclusions. The leading idea of our work lies in the fact that the development of the student's personality as an integrative quality is presented in axiological, cognitive, activity and personal components, formed not only in the educational process, but also in the open area of professional educational institution.